Environmental ethics - Elliot, Robert, 1950- (Oxford ; New York : Oxford University Press, 1995)
The aim of this series is to bring together important recent writings in major areas of philosophical inquiry, selected from a variety of sources, mostly periodicals, which may not be conveniently available to the university student or the general reader. The editor of each volume contributes an introductory essay on the items chosen and on the questions with which they deal. A selective bibliography is appended as a guide to further reading. This volume offers a selection of some of the best and most interesting articles that have been written on ethics and the environment in the past two decades. It constitutes an ideal introduction to the main debates in the area, dealing with issues such as duties to future people, resource conservation, species and wilderness preservation, the relevance of ecology to ethics, ecofeminism, and the tension between political liberalism and environmentalism.
Introduction / Robert Elliot -- I. Discounting Versus Maximum Sustainable Yield / Mary B. Williams -- II. Animal Liberation: A Triangular Affair / J. Baird Callicott -- III. Duties to Endangered Species /Holmes Rolston III -- IV. Faking Nature / Robert Elliot -- V. Duties Concerning Islands / Mary Midgley -- VI. Against the Inevitability of Human Chauvinism /Richard Routley and Val Routley -- VII. Attitudes to Nature /John Passmore -- VIII. Value in Nature and Meaning in Life / Freya Mathews -- IX. Nature, Self, and Gender: Feminism, Environmental Philosophy, and the Critique of Rationalism / Val Plumwood -- X. Can Environmentalists be Liberals? / Mark Sagoff -- XI. Ecological Theory and Value in Nature / Andrew A. Brennan -- XII. Stasis: The Unnatural Value / Colleen D. Clements -- XIII. Philosophical Problems for Environmentalism / Elliott Sober.
Includes index.
Bibliography: p. [249]-251.
Keywords: Environmental ethics